Pengaruh Konsentrasi Ekstrak Bawang Merah (Allium cepa L.) sebagai Zat Pengatur Tumbuh terhadap Pertumbuhan Krisan (Chrysanthemum morifolium) Secara In Vitro - Ridwan, Radhika Nabila Ma’rufi; Edi, Syahmi (Biocaster : Jurnal Kajian Biologi, 2026)
Chrysanthemum (Chrysanthemum morifolium) is a major ornamental plant commodity in Indonesia with a production level of up to 459 million stems. The success of in vitro propagation is largely determined by the use of appropriate Plant Growth Regulators (PGRs). This study aimed to evaluate the performance of shallot (Allium cepa L.) extract as a natural PGR, while determining the optimal dose to support chrysanthemum growth in vitro. The study was conducted at the Laboratory of the Horticulture Main Center (BIH) Gedung Johor, Medan, from October 2025 to January 2026, using a Completely Randomized Design (CRD) that included six concentration levels (K0=0; K1=5; K2=10; K3=15; K4=20; and K5=25 mL L⁻¹), with 10 replications. Data analysis was performed using ANOVA-DMRT for parametric data and Kruskal-Wallis–Dunn for non-parametric data. The study results indicated a significant effect (p < 0.01) on all growth parameters. A concentration of 20 mL L⁻¹ was most effective for organogenesis, producing 15.60 leaves, 7.85 roots, and 3.15 shoots; while 5 mL L⁻¹ was superior for elongation, with plantlets reaching 8.99 cm in height. Concentrations above the optimal dose actually inhibited growth due to the accumulation of phytotoxic compounds. These findings provide a more cost-effective and sustainable chrysanthemum propagation protocol as a substitute for synthetic plant growth regulators.